Dynamic capabilities understanding strategic change in organizations - Helfat, Constance E. (Malden Blackwell Pub, 2007)
Creating, adapting to, and exploiting change is inherently entrepreneurial. To survive and prosper under conditions of change, firms must develop the ?dynamic capabilities? to create, extend, and modify the ways in which they operate. The capacity of an organization to create, extend, or modify its resource base is vital.
Includes bibliographical references (p. [124]-137) and indexes.
Keywords: Organizational change